+0  
 
+1
114
1
avatar+701 

http://prntscr.com/l94xps

thankyou !

 Oct 22, 2018
 #1
avatar+98196 
+2

sqrt [ 4  +  sqrt (63)  / 2 ]  + sqrt [ 4 - sqrt (63 /2) ]

 

Square this

 

4 + sqrt (63/2)  +  2 sqrt [ 4  +  sqrt (63)  / 2 ]  * sqrt [ 4 - sqrt (63 /2) ] + 4 - sqrt(63/2)

 

[ 4 + sqrt (63 / 2)   +    2 sqrt  [ 16 - 63 / 4 ]  + 4 - sqrt (63/2)  ]   =

 

 8  + 2 sqrt [( 64 - 63) / 4  ]  =

 

8 + 2 sqrt ( 1/4)  =

 

8 + 2 (1/2)  =  

 

9

 

Since both  quantities under the original radical are positive, take the  positive square root  of 9  =

 

3

 

 

cool cool cool

 Oct 22, 2018

6 Online Users

avatar